CNT-functionalized electrospun fiber mat for a stretchable moisture-driven power generator. Issue 6 (24th January 2023) - Faramarzi, Paniz; Kim, Byeunggon; You, Jae Bem; Jeong, Soo-Hwan
Abstract : A stretchable moisture-driven power generator (MPG) composed of carbon nanotubes on an electrospun mat is demonstrated. The MPG generated can generate a peak power of 320 nW and shows reliable operation even at 60% applied strain. Abstract : With recent demand for next-generation wearable and stretchable electronics, development of reliable power systems that can accommodate the flexibility and stretchability of devices is necessary. Recently, a moisture-driven power generator (MPG) has been considered as one of the powerful candidates for providing energy to the next-generation wearable and stretchable devices. However, so far, currently developed MPG systems do not meet the stretchability requirements. Here, we report a stretchable MPG formed by layer-by-layer coating of carbon nanotubes on a stretchable electrospun fiber mat. By adding water to the stretchable MPG, an electrical double layer is developed at the interface between the carbon nanotubes and water. Transport of protons (H3 O + ) in water induces the movement of electrons in the carbon nanotubes, inducing a pseudostreaming current. The MPG of 1 cm × 2 cm with 10 μL of deionized water generates a maximum open-circuit voltage ( V OC ) of 419 mV, a maximum short-circuit ( I SC ) current of 1.5 μA, and a maximum power output of 320 nW, depending on the loading of the carbon nanotubes. In addition, 0.6 M NaCl solution enhances the generated V OC (∼800 mV), maximum I SC (13 μA), and maximum power output of 10.4 μW by supplying additional Na + ions to the carbon nanotube surface and reducing the resistance of the device, respectively. Furthermore, MPG can generate a V OC of 600 mV and an I SC of 0.7 μA even when stretched with a strain of 60%. The MPG reported here has the potential to be used as a reliable power generator for wearable and stretchable electronic devices.